Intra-arterial Administration of Placenta-Derived Decidual Stromal Cells to the Superior Mesenteric Artery in the Rabbit: Distribution of Cells, Feasibility, and Safety. Issue 2 (February 2016) - Arnberg, Fabian; Lundberg, Johan; Olsson, Annie; Samén, Erik; Jaff, Nasren; Jussing, Emma; Dahlén, Ulrika; Nava, Silvia; Axelsson, Rimma; Ringdén, Olle; Kaipe, Helen; Holmin, Staffan
Selective administration of mesenchymal stromal cells to the mesenteric arteries is a potential technique to overcome pulmonary trapping and increase the density of transplanted cells in extensive mural inflammation of the intestine, such as in inflammatory bowel disease and graft-versus-host disease. We injected 5 × 10 6 111 In-oxine-labeled human decidual stromal cells (DSCs) to the rabbit superior mesenteric artery (SMA) using clinical routine catheters guided by an angiographical system under sterile conditions. We used longitudinal single-photon emission tomography at 6 h and at 1, 2, and 5 days to assess trafficking and distribution of DSCs. We used digital subtraction angiography, computed tomography, and hematoxylin and eosin stainings to determine biodistribution of cells and to assess safety end points. We found that selective injection of human DSCs to the rabbit SMA does not result in acute embolic complications. Furthermore, we found that IV administration resulted in extensive retention of the radiolabeled DSCs in the lungs, corroborating previous studies on pulmonary trapping. In sharp contrast, selective injections to the SMA resulted in uptake distributed in the intestine supplied by the SMA and in the liver, indicating that this approach could significantly increase the fraction of injected DSCs reaching the target tissue.